STUDENTS’ PERCEPTION ON THE USE OF ENGLISH-SUBTITLED MOVIES TOWARD STUDENTS’ SPOKEN GRAMMAR UNDERSTANDING - Murti Larasati, Tasya; Movi Riana Rahmawanti; Nurhadianty Rahayu (Universitas Wiralodra, 2021)
Grammar is a problematic issue regarding English comprehension for the students, both spoken and written. Several studies showed that English- subtitled movies are effective to develop students' skills in English. Thus, students' behavior in watching English-subtitled movies can be interlinked with their understanding of spoken Grammar. This study aims to find students' perception of using English subtitled movies toward students' Spoken Grammar Understanding. Ten participants who enrolled in spoken grammar course participated in this study. An online closed-ended questionnaire is employed to determine students' perception of using English subtitled movies to their Spoken Grammar Understanding. An online semi-structured interview was then used to clarify and elaborate the students’ view on using English subtitled movies to their Spoken Grammar Understanding further. From the result, the subtitled movies are perceived to impact the students’ spoken grammar understanding significantly. This study implies the use of subtitled movies in English teaching and learning grammar.